2016
DOI: 10.1111/cen.13097
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D treatment in Somali women living in Sweden – Two randomized, placebo‐controlled studies

Abstract: SummaryObjective There is limited information about the prevalence of vitamin D deficiency and the effects of treatment on immigrants. The effects of oral vitamin D intake and UVB treatment on vitamin D status in healthy Somali women living in Sweden were analysed. Design Two studies were carried out; a randomized, doubleblind, placebo-controlled study, with oral drops of 800 IU and 1600 IU cholecalciferol and similar amounts of placebo given daily during 12 weeks and a single-blind, placebo-controlled study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In contrast to the immigrants, sufficient vitamin D status was reported for the majority of Finnish adults in 2012 (10) . Insufficient S-25(OH)D concentrations have also been observed in other studies examining immigrants of East African (16)(17)(18) and other ethnic origin (8,16,19) in the Nordic countries.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In contrast to the immigrants, sufficient vitamin D status was reported for the majority of Finnish adults in 2012 (10) . Insufficient S-25(OH)D concentrations have also been observed in other studies examining immigrants of East African (16)(17)(18) and other ethnic origin (8,16,19) in the Nordic countries.…”
supporting
confidence: 71%
“…Similarly to our study, lower S-25(OH)D concentrations were observed in Somali women (East Africans) than in Finnish women in an earlier study carried out in Finland (12) . In other countries besides Finland, high prevalence of vitamin D deficiency (S-25(OH)D < 30 nmol/l) is commonly reported in Somali subjects (East Africans) (16)(17)(18) . On the contrary, vitamin D status in the general Finnish population has improved over the years and it is satisfactory (10,45) .…”
Section: Discussionmentioning
confidence: 99%
“…Nordic countries have vitamin D deficiency rates below 1% (due to diet or supplementation) and impressively low COVID-19 fatality rates, except Sweden (146,202). In Stockholm, severe vitamin D deficiency is common among displaced Somalis, who with less than 1% of the population have suffered 40% of the COVID-19 fatalities (10,178,203). Indonesia straddles the equator, but its predominately Muslim women have vitamin D levels that are only half that of notoriously low Italy (146).…”
Section: Analyses Of Population Datamentioning
confidence: 99%
“…Somali women, n = 114, aged 18–56 years, with skin type V, who had migrated from latitude 0–10° North (N), and having lived in Sweden, latitude 57° N, for at least 2 years, were recruited during the autumn-winter 2010–2011 on a voluntary basis to participate in a vitamin D treatment trial [18]. The range of their stay in Sweden was 2–23 years, mean 15.1 ± 6.4 and median 18 years.…”
Section: Methodsmentioning
confidence: 99%
“…Many patients from Somalia come to the general practitioners due to these symptoms and the physicians must be aware that vitamin D deficiency is a possible explanatory factor. Supplementation should be given accordingly [18].…”
Section: Introductionmentioning
confidence: 99%